R-Type Fonticins Produced by Pragia fontium Form Large Pores with High Conductance - Látrová, Klára; Dolejšová, Tereza; Motlová, Lucia; Mikušová, Gabriela; Bosák, Juraj; Snopková, Kateřina; Šmajs, David; Konopásek, Ivo; Fišer, Radovan (Journal of bacteriology, 2023)
Phage tail-like bacteriocins are now the subject of research as potent antibacterial agents due to their narrow host specificity and single-hit mode of action. In this work, we focused on the structure and mode of action of fonticins. Fonticins are phage tail-like bacteriocins produced by the Gram-negative bacterium Pragia fontium from the family Budviciaceae . This bacterium produces contractile-type particles that adsorb on the surface of sensitive bacteria and penetrate the cell wall, probably during contraction, in a way similar to the type VI secretion system. We characterized the pore-forming activity of fonticins using both living cells and in vitro model membranes. Using a potassium leakage assay, we show that fonticins are able to permeabilize sensitive cells. On black lipid membranes, single-pore conductance is about 0.78 nS in 1 M NaCl and appears to be linearly dependent on the increasing molar strength of NaCl solution, which is a property of considerably large pores. In agreement with these findings, fonticins are not ion selective for Na + , K + , and Cl − . Polyethylene glycol 3350 (PEG 3350) molecules of about 3.5 nm in diameter can enter the fonticin pore lumen, whereas the larger molecules cannot pass the pore. The size of fonticin pores was confirmed by transmission electron microscopy. The terminal membrane-piercing complex of the fonticin tube probably creates a selective barrier restricting passage of macromolecules. IMPORTANCE Phage tail-like bacteriocins are now the subject of research as potent antibacterial agents due to their narrow host specificity and single-hit mode of action. In this work, we focused on the structure and mode of action of fonticins. According to some theories, related particles were initially adapted for passage of double-stranded DNA (dsDNA) molecules, but fonticins changed their function during the evolution; they are able to form large pores through the bacterial envelope of Gram-negative bacteria. As various pore-forming proteins are extensively used for nanopore sequencing and stochastic sensing, we decided to investigate the pore-forming properties of fonticin protein complexes on artificial lipid membranes. Our research revealed remarkable structural properties of these particles that may have a potential application as a nanodevice.